2010
DOI: 10.1590/s0066-782x2010005000151
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida em pacientes com doença ateroclerótica coronariana grave e estável

Abstract: Background: There are few data on the factors decreasing quality of life (QoL) in patients with coronary artery disease (CAD) before a percutaneous coronary intervention (PCI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
2
7
0
1
Order By: Relevance
“…However, the component Bodily Pain, one of those perceived as most compromised for the participants in our study, was what obtained the best evaluation. (4) The component Role-Physical was perceived as the most compromised in our study, corroborating what was found in one national study (10) and another international study. (4) This component is related to the consequences of physical health, such as reduced quantity of time dedicated to work or other activities, carrying out less tasks than the person would like, and limitations and difficulties performing activities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the component Bodily Pain, one of those perceived as most compromised for the participants in our study, was what obtained the best evaluation. (4) The component Role-Physical was perceived as the most compromised in our study, corroborating what was found in one national study (10) and another international study. (4) This component is related to the consequences of physical health, such as reduced quantity of time dedicated to work or other activities, carrying out less tasks than the person would like, and limitations and difficulties performing activities.…”
Section: Discussionsupporting
confidence: 91%
“…(9) Individuals with established CAD present endangered HRQOL, which can be attributed to a group of factors that include the condition of the disease itself, physical limitations, depressive symptoms, and risk of death, which may intensify progression of the disease. (2,10) Patients who underwent myocardial revascularization (PCI or CABG surgery) present better HRQOL six months after an acute coronary event when compared to the group of patients who were not revascularized. Improvement of HRQOL is related to improvement of physical functioning, reduction of symptoms and, consequently, better coexistence with the chronic illness, which requires efforts by the patient to retard its evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, obesity was related to the physical but not to the mental HRQoL components [11][13], [16][18], [22], [34], [37], [54]. Other studies showed an association between obesity and the mental HRQoL [8], [10], [14], [26], [31], [55], whereas the association was often much weaker compared to the physical components [11], [12], [16]. Our study confirmed a weak but significant inverse cross-sectional relationship between BMI and mental HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…In weight-loss interventions, it can be difficult to distinguish between the effect of the reduced body weight on HRQoL and the effect of the components of the program such as increased physical activity or improved diet. Two studies investigating this difference showed that the individual’s weight loss could not completely but partly explain the beneficial intervention effect on physical HRQoL [55], [56].…”
Section: Discussionmentioning
confidence: 99%
“…Estudos mostraram uma maior incidência de eventos cardiovasculares na população com sintomas depressivos ou baixos escores de indicadores de qualidade de vida. Pacientes com DAC já instalada apresentam qualidade de vida prejudicada e nível elevado de estresse, impostos pela própria condição de doença, limitação física e risco de morte, fechando um círculo vicioso que intensifica a progressão da doença 14 . Na DAC e nas DCV, na perspectiva preventiva ou de tratamento, é importante a participação da família, principalmente no suporte ao idoso.…”
Section: Revisão De Literaturaunclassified